KOMUNIKASI SIMBOLIK MATEN LURIN PADA RITUAL KEMATIAN DI DESA WALANGSAWAH KECAMATAN OMESURI NUSA TENGGARA TIMUR - Florentina Inang; Abbyzar Aggasi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to examine the symbolic meaning contained in the death ritual  of Maten Lurin in Walangsawah Village, Omesuri District, Lembata Regency, East Nusa Tenggara. This ritual is a unique tradition performed for individuals who die without adhering to a formal religion, but still believing in the existence of God. Maten Lurin literally means "bone corpse", and its implementation is loaded with cultural symbols that have social, spiritual, and cultural identity meanings of the community. This study uses a descriptive qualitative approach with data collection techniques through interviews, non-participatory observations, and documentation. The theory of symbolic interaction from George Herbert Mead and Herbert Blumer is used as a cornerstone of analysis to understand the process of forming meaning in social interaction through symbols. The results of the study show that symbols such as old coconuts, stones, hazelnut and rita tree branches, woven cloth (wela), sarongs (lipa), and black cloth (nutaq) function as communication mediums that strengthen the relationship between the human world and ancestral spirits. These symbols not only represent the identity of the deceased, but also become a means to maintain spiritual harmony and traditional continuity in society. Thus,  the Maten Lurin ritual  reflects the sustainability of local cultural values and the importance of symbolic communication in maintaining the identity and social balance of the Walangsawah community.